Integrasi Nilai-Nilai ar-Rahman dan ar-Rahim dalam Pengembangan Kecerdasan Anak Usia Dini - Ahmad Zohdi; Murzal (UIN Mataram, 2023)
The problem in this research is knowing the application of ar-Rahman and ar-Rahim values as a strategic approach in developing intelligence in early childhood. The aim of this research is to determine the application of ar-Rahman and ar-Rahim values as a strategic approach in developing early childhood intelligence. The method used is a descriptive method with a quantitative approach. The research results showed that teachers at Al-Mahsun Khidir Dasan Tapen Kindergarten had integrated the values of ar-Rahman and ar-Rahim in developing multiple intelligence consisting of: linguistic intelligence, logical-mathematical intelligence, spatial intelligence, physical-kinesthetic intelligence, musical intelligence, intrapersonal intelligence, interpersonal intelligence, naturalist intelligence and spiritual intelligence in the learning process carried out.